Government Strategy in Implementing the Good Governance during COVID-19 Pandemic in Indonesia - Muhamad Azhar (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
Countries in the world are currently facing shocks and challenges that are not easily faced with the COVID-19 pandemic, including Indonesia. Under these conditions, the performance of the governance system in dealing with a pandemic is tested transparently in public. The implementation of good governance by the government itself is carried out by steps and decisions that will be taken and implemented by the government to the community in order to suppress the positive number of COVID-19. The application of good governance also needs support other crucial elements, one of which is public communication. Keywords: Government Strategy, Good Governance, COVID-19, Pandemic, Abstrak Negara-negara di dunia saat ini sedang menghadapi guncangan dan tantangan yang tidak mudah dihadapi dengan pandemi COVID-19, tidak terkecuali Indonesia. Di bawah kondisi ini, kinerja sistem pemerintahan dalam menghadapi pandemi diuji secara transparan di depan umum. Implementasi dari good governance oleh pemerintah sendiri dilakukan dengan Langkah-langkah dan keputusan yang akan diambil dan diterapkan oleh pemerintah kepada masyarakat demi menekan angka positif COVID-19. Penerapan dari good governance pun perlu dukungan dari elemen krusial lain, salah satunya yaitu komunikasi public. Hal ini bertujuan agar pendekatan yang dilakukan ke publik untuk menaati segala kebijakan menuai hasil yang maksimal dalam keberhasilan menumpas pandemik ini Kata Kunci: COVID-19, tata kelola pemerintahan yang baik, komunikasi